An Assessment Of Multicultural Training Practices: A Malaysian Perspective - Gunaratnam, Shoba (2001)
This study investigates how organization utilize multicultural training program from a training process approach. In compilation of this project, two major methods of the data collection were used to collect the information in the study: (1) questionnaires and (2) document analysis.